(untitled) (JURNAL KEPERAWATAN, 2018)
Abstract : Breast Milk is the best food for babies, because the content of very special and perfect its nutrition value, as well as in accoordance with the needs of the growing baby flower. During breast feeding mothers need support one family support. During breast feeding mothers need support on a family support. Familly support is a major external factors affect the success of Exclusive breast milk. The Purpose of the research is known to support the family relationship with exclusive breast feeding on infants in Clinic Ranotana Weru. Design Research is descriptive research of correlative with the approach of Cross Sectional. Samples in this research is the mother who has a baby aged 6-12 months as much as 103 respondents in the method of is simple random sampling. The Result of the Research using statistical test of Chi- Square with a confidence level of 95% (Î±=0,05%) obtained value p=0,000 < (Î±) 0,05%. Research Findings of this study showed that there is a significant relationship between family support with exclusive breast feeding on infants in Clinic Ranotana Weru. Keywords : Family support, Exclusive breast milk Abstrak : Air Susu Ibu (ASI) adalah makanan terbaik untuk bayi, karena kandungan gizinya sangat khusus dan sempurna serta sesuai dengan kebutuhan tumbuh kembang bayi. Selama Ibu menyusui ibu membutuhkan dukungan salah satunya dukungan keluarga. Dukungan keluarga merupakan faktor eksternal yang paling besar pengaruhnya terhadap keberhasilan ASI Eksklusif. Tujuan Penelitian diketahui hubungan dukungan keluarga dengan pemberian asi eksklusif pada bayi di Puskesmas Ranotana Weru. Desain Penelitian merupakan penelitian deskriptif korelatif dengan pendekatan cross sectional. Sampel pada penelitian ini adalah ibu yang mempunyai bayi berusia 6-12 bulan sebanyak 103 responden secara metode simple random sampling. Hasil Penelitian menggunakan uji statistik Chi-Square dengan tingkat kepercayaan 95% (Î±=0,05%), didapatkan nilai p-value=0,000 < (Î±) 0,05%. Simpulan hasil penelitian ini menunjukkan bahwa ada hubungan yang signifikan antara dukungan keluarga dengan pemberian ASI eksklusif pada bayi di Puskesmas Ranotana Weru. Kata Kunci : Dukungan keluarga, Asi eksklusif